Trends on the Cellulose-Based Textiles: Raw Materials and Technologies - Felgueiras, Catarina; Azoia, Nuno G.; Gonçalves, Cidália; Gama, Miguel; Dourado, Fernando (Frontiers in Bioengineering and Biotechnology, 2021)
There is an emerging environmental awareness and social concern regarding the environmental impact of the textile industry, highlighting the growing need for developing green and sustainable approaches throughout this industry’s supply chain. Upstream, due to population growth and the rise in consumption of textile fibers, new sustainable raw materials and processes must be found. Cellulose presents unique structural features, being the most important and available renewable resource for textiles. The physical and chemical modification reactions yielding fibers are of high commercial importance today. Recently developed technologies allow the production of filaments with the strongest tensile performance without dissolution or any other harmful and complex chemical processes. Fibers without solvents are thus on the verge of commercialization. In this review, the technologies for the production of cellulose-based textiles, their surface modification and the recent trends on sustainable cellulose sources, such as bacterial nanocellulose, are discussed. The life cycle assessment of several cellulose fiber production methods is also discussed.